Granuloma Caused by Carbon Deposition in the Dermis. (20th February 2014) - Shibuya, Rintaro; Endo, Yuichiro; Fujisawa, Akihiro; Tanioka, Miki; Miyachi, Yoshiki
Abstract : Pencil core granuloma is characterized by a delayed foreign-body reaction against retained fragments of pencil lead. Previous case reports presented pencil core granuloma resembling malignant melanoma, haemangioma, or soft tissue sarcoma. We present a case of pencil core granuloma arising from the palm 25 years after the initial injury. The patient presented a bluish nodule that had been present over 25 years before. The nodule initially measured 5 mm in diameter. However, five years before presentation, it suddenly enlarged to the size of 30 mm during six months. Computed tomography (CT) of the lesion revealed a linear radiopaque structure of 8 mm long with a mass on its distal end. Surgical resection revealed a bluish muddy mass and pencil lead. Histological examination revealed degenerative tissue with calcification surrounded by massive amounts of black granular material in the middle and lower dermis.